„Ogród sztuk”. Kilka uwag o "Orkiestrze" Zbigniewa Rybczyńskiego - Grodź, Iwona (My University, 2013)
The garden presents itself as an area consciously created by the human being. Its representation is usually actualized in opposition both to what is natural and to what is artificial (e.g. to a city). Over many years now, the garden has been been considered to be a “cultural fossil”, and as such, an object of importance for literary critics, film critics, art historians, musicologists etc., and an anthropological phenomenon, which is demonstrated by contemporary juxtapositions of aesthetics with environmental science, pace Gernot Böhme, or the transcultural aesthetics promoted by Wolfgang Welsch). At this stage, we are very close to full understanding of the phenomenon of garden-topos, as well as the numerous garden metaphors. In Zbigniew Rybczyński’s film "Orkiestra" there are several areas of author’s interest in the garden created and filmed on a theatrical stage. The garden as a space of life-renewal, symbol of birth and metaphysical rebirth, a renewed experience of fulness. The garden as a space of ordered life, positive energy, areas of joy liberation, a synonym of goodness and ideals. Finally, as the symbol of return to creation, beauty, to the first beginning, to civilized and tame nature.
“The Garden of Arts”. Several Remarks on Zbigniew Rybczyński’s "Orkiestra" [The Orchestra]
Keywords: Zbigniew Rybczyński; space in artwork (literature, film, painting etc.); garden metaphors; correspondence of arts; cultural research; cultural memory